1999
DOI: 10.1200/jco.1999.17.10.3075
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity and Prognosis in Primary Breast Cancers

Abstract: Telomerase activity level was associated with the proliferative index of invasive breast cancers, but its measurement in samples from this group of nonmetastatic breast cancer patients did not predict survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 18 publications
1
18
0
2
Order By: Relevance
“…Nevertheless, almost a third of our DCIS samples were telomerase-negative, whereas all invasive cancer samples were telomerase-positive. Thus, telomerase activation may indeed be occurring in DCIS, since invasive breast cancer is usually telomerase positive even in early stages (Carey et al, 1998), and limited data on atypical hyperplasia (Poremba et al, 1998) suggest that earlier lesions are telomerase negative. While the source of low but detectable levels of telomerase in ®broadenomas (Hiyama et al, 1996;Poremba et al, 1998) will need to be investigated further, these lesions do not generally pose diagnostic di culties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, almost a third of our DCIS samples were telomerase-negative, whereas all invasive cancer samples were telomerase-positive. Thus, telomerase activation may indeed be occurring in DCIS, since invasive breast cancer is usually telomerase positive even in early stages (Carey et al, 1998), and limited data on atypical hyperplasia (Poremba et al, 1998) suggest that earlier lesions are telomerase negative. While the source of low but detectable levels of telomerase in ®broadenomas (Hiyama et al, 1996;Poremba et al, 1998) will need to be investigated further, these lesions do not generally pose diagnostic di culties.…”
Section: Discussionmentioning
confidence: 99%
“…Telomerase activity has been proposed as a potentially useful tumor marker in breast cancer, since it has been detected in most invasive breast cancers, but not in benign breast lesions, with the possible exception of some ®broadenomas (Kim et al, 1994;Meeker and Co ey, 1997;Nelson, 1996;Shay and Bacchetti, 1997). In several studies of primary invasive breast cancers, approximately 75 ± 95% of tumors demonstrate telomerase activity, while 5 ± 25% are telomerase-negative (Bednarek et al, 1997;Carey et al, 1998;Hiyama et al, 1996;Landberg et al, 1997;Nawaz et al, 1997). Initial results suggested that smaller, lymph nodenegative tumors were more likely to be telomerasenegative than their larger, lymph node-positive counterparts (Hiyama et al, 1996;Kim et al, 1994), and it was postulated that telomerase activity is acquired during tumor progression to metastasis (Hiyama et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mokbel et al [22] , using a PCR-based assay, showed that telomerase activity in breast cancer is not associated with nodal status or disease outcome. Carey et al [23] , studying 203 invasive breast cancers by the TRAP method, found that telomerase activity was associated with the proliferative index but did not predict survival. Nawaz et al [24] reported no significant difference in telomerase expression between node-negative and nodepositive breast carcinoma, as well as with tumor size and hormonal status.…”
Section: Discussionmentioning
confidence: 99%